Scale dependency of Liolaemus lizards' home range in response to different environmental variables. Issue 6 (17th March 2016) - Stellatelli, Oscar Aníbal; Block, Carolina; Moreno-Azócar, Débora Lina; Vega, Laura Estela; Isacch, Juan Pablo; Cruz, Félix Benjamín
Abstract : Animal habitat-use patterns cannot be isolated from scale issues. Consequently, multi-scale studies provide a complete characterization of ecological patterns that can further explain the observed variation. Liolaemus constitutes the world's second most speciose lizard genus. In this study, we assessed the relationships between home range size and environmental variables at 3 different spatial scales. The study at a local and regional scale was focused on the habitat specialist Liolaemus multimaculatus . The lizard's home range was calculated using the minimum convex polygon method in populations from grassland sites of the coastal sand dunes of the Argentinean Pampas under 2 different conditions, with or without forestations of Acacia longifolia . On the other hand, at a geographical scale we considered the evolutionary implications of 20 species of Liolaemus. Home range size, phylogeny, ecological, environmental, and climatic data were obtained from the literature and remote sensing. L. multimaculatus home range varied from 12.66 to 570.00 m. Regionally, this species had smaller home ranges in forested habitats (X ¯ : 94.02 m 2 ) compared with the non-forested sites (X ¯ : 219.78 m 2 ). Habitat structure, vegetation types, and food availability would explain the space use at finer scales. When the 20 species of Liolaemus were considered, high mean air temperature and broad thermal amplitudes showed an inverse relationship with home range size. Neither net primary productivity nor phylogeny was good predictors for home range variation at geographical scale. This study highlights the scale dependence of the explicative capability of a set of environmental and intrinsic variables on home range patterns.